Evaluation of a Telehealth Paediatric Asthma and Allergy Clinic Patient Follow-Up During the COVID-19 Pandemic - Sarah J. Prior; Gaylene Bassett; Emmeline Van Beek; Claire Griffiths; Smriti Sinha; Shrima Shrestha; Sukhwinder Singh Sohal; Heinrich Christoph Weber (Children)
Background/Objectives: The COVID-19 pandemic created many challenges for health services, particularly during lockdown periods. Asthma is one of the most common childhood conditions, and children with asthma are generally cared for in an outpatient setting. In regional Northwest Tasmania, during the COVID-19 lockdowns, asthma and allergy outpatient clinic services were transferred to a virtual platform in the form of telehealth appointments for routine consultations. This study aims to explore the patient and family perspectives of a telehealth outpatient asthma review service in a regional area. Methods: We utilised a mixed-methods approach, interviewing parents and children who attended the clinic via telehealth and collating routine clinical audit data collected during the same period. Results: Sixty-three patient reviews were audited, with a mean age of 9.79 years. Since their last review, 13% visited their GP, 9% presented to the ED, 6% were hospitalised, and 19% had changes in their treatment plan. Interviews highlighted three main themes: (i) telehealth is a convenient strategy for routine asthma and allergy review appointments, (ii) barriers associated with using telehealth are a minor concern for parents of children with asthma and allergy routine appointments, and (iii) shared decision-making between clinicians and parents of children with asthma and allergy around the type of appointment required is valued. Conclusions: We demonstrated that the benefits of telehealth include implementing treatment changes and facilitating access to care for children living in rural and remote areas.